(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
As time progresses, new challenges inevitably arise, a common phenomenon in social development. In such situations, there are two main approaches for finding solutions. One is to explore and adopt new methods, while the other relies on historical experience, drawing upon a nation’s religious, cultural, and educational values, and interpreting them in a way that aligns with modern needs. This article discusses the interpretation of values such as justice, social assistance, and unity in Islam, which is regarded as a sacred religion, and examines the positive aspects of applying these principles in today’s context.